Population size and breeding success of the Icelandic Whooper Swan Cygnus cygnus: results of the January 2005 international census - Worden, Jenny; Crowe, Olivia; Einarsson, Ã“lafur; Gardarsson, Arnthor; Mcelwaine, Graham; Rees, Eileen C (Wildfowl, 2013)
The fifth international census of Whooper Swans in Britain, Ireland and Iceland was undertaken in January 2005 to determine the size and winter distribution of the Icelandic-breeding Whooper Swan population. A total of 26,366 Whooper Swans was counted, of which 37% were recorded in the Republic of Ireland (9,748 birds), 25% in England (6,480), 16% in Northern Ireland (4,331), 16% in Scotland (4,142), 6% in Iceland (1,556) and < 1% in Wales and the Isle of Man (109). A comparison with results of the previous international census made in January 2000 found that the numbers of swans counted had increased in all countries except Wales. There was also an increase in the proportion of swans wintering in England and Scotland, compared with numbers elsewhere in the range. The substantial increase in numbers of birds in England was not accompanied by a significant increase in the number of flocks recorded, and distribution remains concentrated at relatively few sites. In contrast, there was a decrease in the number of flocks found in the Republic of Ireland and an increase in Scotland. As with previous censuses, birds were recorded most commonly on pasture in Britain and Ireland, although use of arable land has increased over the last three censuses from 7% to 27%. The total number of Whooper Swans counted in 2005 was the highest census total to date. This represents a 26.4% increase on numbers recorded in the January 2000 census, and a 66.4% increase in population size over the last decade.